2020
DOI: 10.1158/1078-0432.ccr-19-3271
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thymidine Kinase Activity as a Biomarker in Patients with Luminal Metastatic Breast Cancer Treated with Palbociclib within the TREnd Trial

Abstract: Purpose: Thymidine kinase 1 (TK1) is downstream to the CDK4/ 6 pathway, and TK activity (TKa) measured in blood is a dynamic marker of outcome in patients with advanced breast cancer (ABC). This study explores TK1 as a biomarker of palbociclib response, both in vitro and in patients with ABC.Experimental Design: Modulation of TK1 levels and activity by palbociclib were studied in seven estrogen receptor-positive breast cancer cell lines: sensitive (PDS) and with palbociclib acquired resistance (PDR). TKa was a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 31 publications
3
34
1
Order By: Relevance
“…In contrast, no significant association was observed between baseline pTKa and PFS. In the present study, we did not find a predictive impact of the variation of pTKa between baseline and 4 weeks, regardless of the increase/decrease cutoff used (data not shown), unlike these other studies [13,24,25]. These contradictory results could be explained by several factors.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In contrast, no significant association was observed between baseline pTKa and PFS. In the present study, we did not find a predictive impact of the variation of pTKa between baseline and 4 weeks, regardless of the increase/decrease cutoff used (data not shown), unlike these other studies [13,24,25]. These contradictory results could be explained by several factors.…”
Section: Discussioncontrasting
confidence: 96%
“…The EFECT trial [13] suggested that patients whose sTKa increased from baseline while on endocrine therapy had a significantly shorter time to progression (3.39 months, 95%CI 2.14-4.11) than those in whom sTKa did not increase (5.39 months, 95%CI 4.01-6.68) (p = 0.0045). More recently, the TREnd trial [25] showed a significant correlation between the 4-week variation of pTKa and PFS in ER+/HER2− MBC patients treated with palbociclib (alone or in combination with endocrine therapy following progression during a previous line of therapy). In the TREnd study, pTKa increase (n = 33 patients) was associated with shorter PFS (median PFS for the group with increasing pTKa = 3.0 months, 95%CI [2.7-NA] versus 9 months for stable or decreasing pTKa, 95%CI [5.8-12.0], p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we observed alterations in nucleotide metabolism in MCF7/pS vs. MCF7/pR cells. Importantly, these results are in line with previous reports indicating that increased expression of thymidine kinase-1 (TK1), an enzyme of the pyrimidine salvage pathway, correlates with poor prognosis in breast cancer patients treated with palbociclib [52][53][54][55].…”
Section: Discussionsupporting
confidence: 91%
“…The hypothesis that baseline TKa or early changes in TKa levels might be prognostic in patients with HR+/HER2− MBC treated with CDK4/6i was then explored in TREnd [ 29 ]. In this trial, comparing the efficacy and safety of single-agent palbociclib vs. palbociclib plus the ET previously received for MBC, baseline TKa was not a poor prognostic factor.…”
Section: The Role Of Thymidine Kinase-1 Serum Activitymentioning
confidence: 99%
“…In this trial, comparing the efficacy and safety of single-agent palbociclib vs. palbociclib plus the ET previously received for MBC, baseline TKa was not a poor prognostic factor. However, patients showing an increase in TKa after one month of treatment had a worse PFS compared to those without increase, suggesting TKa dynamics might have a role as an early marker of resistance to palbociclib [ 29 ].…”
Section: The Role Of Thymidine Kinase-1 Serum Activitymentioning
confidence: 99%